(untitled) (Altre Modernità, 2012)
This study constitutes a further development of my doctoral thesis For a Methodology of Translation Criticism: the Italian Translations of The Secret Sharer by Joseph Conrad, where the importance of the translational metalanguage was discussed. In the first section of this paper several definitions of translation and rewriting (mainly by Eco, Bassnet and Lefevere, and Torop) are reviewed, thus highlighting contrasting positions concerning the very definition thereof. The main characteristics of an Italian version of The Secret Sharer for young readers – L’ospite segreto translated by Pieroni and Liberio – are listed, showing the editing and translating strategies underlying this specific text in which the target reader is very different from the source reader. The role of the target reader in translation practice is eventually examined, by stressing the vital status of metalanguage in translation criticism.